Creating Android-based System Aiding Tebuireng Waste Bank Management using Looker Studio - sukmo, guruh; Wira Ghani, Sulung Rahmawan (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Due to the growing influx of visitors in the Tebuireng area, there has been a substantial rise in the accumulation of waste. Bank Sampah Tebuireng (BST) has been established as a concrete effort to address the negative consequences arising from the increasing accumulation of waste. However, the BST still relies on manual data management, which is prone to errors and lacks efficiency. Therefore, the development of an efficient and effective information system becomes crucial. This research aimed to develop an Android-based information system using Kodular and utilize Looker Studio for dashboard visualization for waste bank management in the Tebuireng area. The development methodology included requirement analysis, system design, implementation, and testing. The Android-based information system encompassed features such as transportation, sorting, waste sales, as well as data reporting and analysis. Users could access this system through a user-friendly Android application. Data visualization using Looker Studio displayed interactive graphs, diagrams, and tables for monitoring and analyzing waste bank management data in Tebuireng. The system testing involved evaluation through black box testing. This research has created a user-friendly Android system for Bank Sampah Tebuireng. The system streamlines waste transportation, sorting, and sales processes. Furthermore, this research utilizes Looker Studio for data visualization and interactive reporting, making it user-friendly for day-to-day use and an effective tool for waste management data analysis. Keywords: Bank Sampah Tebuireng, Android, Kodular, Looker Studio, Black Box Testing.